2008
DOI: 10.1029/2007wr005990
|View full text |Cite
|
Sign up to set email alerts
|

Near‐surface soil moisture assimilation for quantifying effective soil hydraulic properties using genetic algorithm: 1. Conceptual modeling

Abstract: We used a genetic algorithm (GA) to identify soil water retention θ(h) and hydraulic conductivity K(h) functions by inverting a soil‐water‐atmosphere‐plant (SWAP) model using observed near‐surface soil moisture (0‐5 cm) as search criterion. Uncertainties of parameter estimates were estimated using multipopulations in GA and considering data and modeling errors. Three hydrologic cases were considered: (1) homogenous free‐draining soil column, (2) homogenous soil column with shallow water table, and (3) heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 66 publications
3
84
0
Order By: Relevance
“…Feasible ranges of the parameters (i.e., search spaces in a modified-microGA) for each model were defined based on literature related to the model parameter sensitivity and to accommodate a diversity of soils ranging from clay to sandy loam Liu et al, 2004;Ines and Mohanty, 2008;Rosero et al, 2010;Shin et al, 2012].…”
Section: Soil Parameters Of the Hydrological Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Feasible ranges of the parameters (i.e., search spaces in a modified-microGA) for each model were defined based on literature related to the model parameter sensitivity and to accommodate a diversity of soils ranging from clay to sandy loam Liu et al, 2004;Ines and Mohanty, 2008;Rosero et al, 2010;Shin et al, 2012].…”
Section: Soil Parameters Of the Hydrological Modelsmentioning
confidence: 99%
“…They showed that GA found better optimized model parameters than others, although a large number of computational resources were required. Further, the near-surface [Ines and Mohanty, 2008] and layer-specific data assimilation [Shin et al, 2012] approaches using GA coupled with SWAP based on inversion model were developed for quantifying effective soil hydraulic properties in the homogeneous and heterogeneous soil profiles. Their findings indicated that the estimated effective soil parameters at the near-surface and subsurface layers can be adequately conditioned by GA.…”
mentioning
confidence: 99%
“…With the restarting technique, the MOGA provides new genetic materials through the creep and jump mutation operators [Ines and Honda, 2005]. The MOGA always remembers the previous (gÀ1) elite chromosomes and reproduce in the next generation [Ines and Mohanty, 2008a]. We integrated a random resampling (ensemble e) algorithm (IBM Programmers' Guide) [Efron, 1982] into the MOGA for searching more unknown spaces, called EMOGA.…”
Section: Deterministic Downscaling Algorithm (Dda)mentioning
confidence: 99%
“…GA is one of the existing powerful search algorithms developed by Holland [18] and Goldberg [24]. To date, GAs have been extended/improved through various updated versions [24][25][26][27][28][29]. Parameters (P 1 = {CN i = 1,…,M }; P 2 = {EMC j = 1,…,N }) to be searched are represented by chromosomes (genes) in an array.…”
Section: Overview Of the L-thiamentioning
confidence: 99%